Rational design of pyrrole derivatives with aggregation-induced phosphorescence characteristics for time-resolved and two-photon luminescence imaging - Jianhui Yang (Nature Portfolio, 2021)
Aggregation-induced emission (AIE) fluorescence probes are indispensable for biomedical imaging, however, interference with tissue autofluorescence results in low signal-to-noise ratio limiting the development of bioimaging with AIE materials. Here the authors develop AIEgen room-temperature phosphors with long emission lifetimes efficiently eliminating intereference with the background signal in imaging.